PENGELOLAAN PELABUHAN PERIKANAN DALAM PENINGKATAN PENDAPATAN PAD (PENINGKATAN PENDAPATAN ASLI DAERAH) DI KOTA PEKALONGAN - CAHYANTAMA DWI RIANTO (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Fishing Port Pekalongan in the field of economic development, in particular Revenue requires a balance among regulations, government agencies, and society. Local government Pekalongan has the authority to regulate the importation policy of revenue (PAD) and expenditure Pekalongan city . Nusantara Fishery Port Pekalongan is that generates source non tax received state (PNBP). Functions The general company Ocean Fishery Port (PPS) as a provider of Fishing Port facilities which the result from facilities is input of itself . its Different from Department of Agriculture, Livestock and Marine (DPPK), which serves to make the policy Regulation (Regulation) in a form of retribution Fish Auction Place (TPI), is that a source of revenue (PAD) Pekalongan city. Therefore Fishing Port is expected to be managed in a synergistic or low an institution, if over authority between VAT Housing Department of Agriculture Livestock and Marine until can increase revenue and improve the welfare of fishermen Pekalongan